Use of focussed beam reflectance measurement (FBRM) for monitoring changes in biomass concentration (Erratum) - Whelan, Jessica (2012)
The potential of focussed beam reflectance measurement (FBRM) as a tool to monitor changes in biomass concentration was investigated in a number of biological systems. The measurement technique was applied to two morphologically dissimilar plant cell suspension cultures, Morinda citrifolia and Centaurea calcitrapa, to a filamentous bacteria, Streptomyces natalensis, to high density cultures of Escherichia coli and to a murine Sp2/0 hybridoma suspension cell line, 3–2.19. In all cases, the biomass concentration proved to be correlated with total FBRM counts. The nature of the correlation varied between systems and was influenced by the concentration, nature, size and morphology of the particle under investigation.